The Fifth International Kharkov Symposium on Physics and Engineering of Microwaves, Millimeter, and Submillimeter Waves (IEEE C
DOI: 10.1109/msmw.2004.1345801
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of HTS Josephson junctions with the surface wave resonator

Abstract: Microwave properties of the surface wave resonator (SWR) consist of high-temperature superconductor (HTS) film on dielectric substrate were investigated. The analysis of the systems is made for continuous HTS film and for a film with an array of HTS Josephson junctions (JJ). In the last case it was revealed the Josephson junction synchronization effect, occurred under the influence of electromagnetic field (EMF) of the SWR. Due to this effect it is possible to make devices with synchronized array of junctions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Provided the conditions → ∞ and = 1, the examined resonance structure is the plate of a real metal with finite lateral dimensions × and is located in the free space. This structure is the simplest case of the SEMWR on the basis of a conducting plate (film) with a finite thickness [6,8,9,12,13]. But if < ∞ and ≥ 1, the RFM-NMI-IM resonance structure can be identified with an SEMWR (layer of a real metal on a dielectric substrate) arranged on the wall surface in a rectangular waveguide (the ideal metal screen).…”
Section: Surface Magnon-plasmon-polaritons In the Real Ferromagnetic mentioning
confidence: 99%
See 3 more Smart Citations
“…Provided the conditions → ∞ and = 1, the examined resonance structure is the plate of a real metal with finite lateral dimensions × and is located in the free space. This structure is the simplest case of the SEMWR on the basis of a conducting plate (film) with a finite thickness [6,8,9,12,13]. But if < ∞ and ≥ 1, the RFM-NMI-IM resonance structure can be identified with an SEMWR (layer of a real metal on a dielectric substrate) arranged on the wall surface in a rectangular waveguide (the ideal metal screen).…”
Section: Surface Magnon-plasmon-polaritons In the Real Ferromagnetic mentioning
confidence: 99%
“…Note that just such SEMWRs on the basis of a conducting film deposited onto a dielectric substrate are used in practice. For the efficient excitation of oscillations in the SEMWR, the latter is mounted inside a rectangular waveguide [6][7][8][9][10][11][12][13].…”
Section: Surface Magnon-plasmon-polaritons In the Real Ferromagnetic mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it was shown that, in a below-cutoff rectangular waveguide, the spectrum of SEWR natural oscillations is substantially rarefied, which can be used for the creation of more efficient microwave devices [25,26]. The obtained results were summarized in [23,24,27].…”
Section: Physics and Applications Of High-temperature Superconductivitymentioning
confidence: 99%